John Paul II, the right to life and abortion - Bauer, Nicolas (Chrześcijaństwo-Świat-Polityka, 2023)
John Paul II formulated the prohibition of killing an innocent person in terms of natural Human Rights. He advocated in favour of the right to life of unborn children, through diplomacy and action at the United Nations. The Polish Pope opposed both the claims and the methods of the pro-abortion lobby. This article examines news of this worldwide battle, analysing both Human Rights Law and the power relations surrounding abortion. Nearly thirty years after the Cairo Conference (1994), unborn children have not been excluded from the protection of the right to life and an international obligation to legalize abortion has never been created. However, the assaults of the pro-abortion lobby are as strong as during the 1990s. The entryism of this lobby has even created dysfunctions in the international institutions themselves, thus affecting and losing their impartiality.